Antioxidant effect and chemical composition of Ananas comosus [L.] Merr. peels from Peruvian Northern [Efecto antioxidante y composición química de las cascaras de Ananas comosus [L.] Merr. del Norte Peruano] - Benites J. (2019)
Pineapple peels has several beneficial properties including antioxidant activity. We investigated the antioxidant effect of five different peels of pineapple lyophilized extracts, not adsorbed and adsorbed onto Amberlite. They were examined using total phenolic contents (TPC), antioxidant effect by 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging and ferric reducing antioxidant power (FRAP). In addition, we analyzed the chemical composition by HPLC-ESI-QTOF-MS/MS. The main constituents of pineapple peels were tentatively identified as quercetin glycosides and N,N’-diferuloylspermidine. We conclude that the antioxidant activity in pineapple peels from District of Poroto, Province of Trujillo, Region of La Libertad, can be associated with the presence of flavonoid and spermidines. © 2019, Universidad de Santiago de Chile. All rights reserved.